Santri sebagai Motor Public Relations: Analisis Program Pemberdayaan di Lembaga Ittihadul Muballighin Lirboyo - Nur Alif Abdul Kholik (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
As an integral part of the Islamic education system in Indonesia, Islamic boarding schools (pondok pesantren) play a crucial role in enlightening the nation—not only in terms of knowledge and character development but also through their contributions to educational advancement. Public relations (humas) within the pesantren environment serves as a strategic platform to prepare students (santri) for effective interaction with the broader community. This study explores the objectives, forms, implementation, and benefits of student empowerment in public relations at the Ittihadul Muballighin Institute (LIM) of Lirboyo Islamic Boarding School in Kediri. Employing a qualitative approach with a case study method, the research reveals that: (1) the objectives of student empowerment in public relations encompass cognitive, affective, and psychomotor domains; (2) empowerment is realized through student involvement in educational, cultural, and institutional activities; (3) implementation proceeds through four stages: planning, organizing, execution, and evaluation; and (4) these activities strengthen the relationship between the pesantren and the surrounding community, fostering mutual understanding and public trust. Moreover, they provide valuable experiential learning opportunities for students, equipping them for future community engagement.